2011
DOI: 10.1179/107902610x12883422813624
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital transport of patients with spinal cord injury in Nigeria

Abstract: Background: A well-organized and efficient prehospital transport is associated with improved outcome in trauma patients. In Nigeria, there is paucity of information on prehospital transport of patients with spinal cord injury (SCI) and its relation to mortality. Objective: To determine if prehospital transportation is a predictor of mortality in patients with SCI in Nigeria. Design: Prospective cohort study Methods: Prehospital transport related conditions, injury arrival intervals and persons that brought pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…There are no standby paramedics or emergency services in Tanzania for basic life support before and immediately on arriving at the hospital [20,21] therefore there is a high chance that severely injured individuals with TSCI die before they get to the hospital or at the emergence department before being admitted. Pre hospital mortality could also be due to delay of the injured person to be admitted to the appropriate health facility as in Nigeria [22] where a delay of up to 24 hours was reported. Those who die before investigations and admittance into the ward are normally not diagnosed with TSCI before death and this adds to the missed cases.…”
Section: Discussionmentioning
confidence: 99%
“…There are no standby paramedics or emergency services in Tanzania for basic life support before and immediately on arriving at the hospital [20,21] therefore there is a high chance that severely injured individuals with TSCI die before they get to the hospital or at the emergence department before being admitted. Pre hospital mortality could also be due to delay of the injured person to be admitted to the appropriate health facility as in Nigeria [22] where a delay of up to 24 hours was reported. Those who die before investigations and admittance into the ward are normally not diagnosed with TSCI before death and this adds to the missed cases.…”
Section: Discussionmentioning
confidence: 99%
“…table; for all online suppl. material, see www.karger.com/doi/10.1159/000382079) [7,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107]. The study duration ranged from less than one year to more than 50 years, and included data beginning in 1935 until 2009.…”
Section: Resultsmentioning
confidence: 99%
“…In Pakistan, Rathore et al (2008) reported that 22.2% were evacuated by ambulance and the rest travelled in cars, jeeps and transport vehicles. In Nigeria, Ahidjo et al (2012) found that only 5.4% of the injured were transferred by ambulance, while Nguyen et al (2008) found this to be only 4% in Vietnam. In contrast, 93% of the injured in Sweden used the services of an ambulance (Divanoglou et al, 2010), and in Canada 41% were transported by ground ambulance, 54% by helicopter, and 5% by fixed-wing aircraft (Burney et al, 1989).…”
Section: Outcome Of Rehabilitationmentioning
confidence: 99%